The Mystery of Saving in Latin America - Oscar Becerra; Eduardo A. Cavallo; Ilan Noy (Inter-American Development Bank (IDB), 2015)
Using reduced-form regression models, this paper shows that average predicted private saving rates in Latin America and the Caribbean (LAC) are significantly lower than in other regions, particularly Emerging Asia (about 4 percentage points of GDP on average). Predicted public saving rates in LAC are also lower than in Emerging Asia, but by a smaller margin (1 percentage point of GDP on average). It is further shown that LAC private saving rates are below the region-specific prediction by approximately 1. 5 percentage points of GDP on average. Finally, it is found that a greater reliance on external savings does not fully close the negative estimated private saving gap, reducing it by less than 1 percentage point. No gap is found in the case of public saving rates, suggesting that the lower predicted public saving rate in LAC is accounted for by the known determinants of fiscal policy.
hdl:11319/7311
Keywords: E21; 330; Saving rates; Saving gap; Determinants of saving; Private saving; Public saving